The - Brown, Sallie A. (Roxbury Pub. Co., 2001)
This text offers a metacognitive approach that develops an awareness of students' thought processes, study strategies, attitudes, and habits. It discusses how students can learn more in less time and with greater ease and confidence, and the book's modular format accommodates the emerging needs of any learning environment